Features of automation of gas meter verification process using bell-provers - Гук, Олег; Матіко, Федір; Скібель, Павло (Моделювання, керування та інформаційні технології, 2025)
This paper presents an analysis of a bell-prover used for the metrological verification of gas flow meters and gas meters, highlighting its advantages and disadvantages. Based on the analysis of scientific sources and experimental studies of reference bell-provers, it was established that these installations are the most accurate means for testing and calibrating gas meters. However, their metrological characteristics significantly depend on the operating conditions, particularly on working pressure, sealing liquid level, and ambient temperature. Variations in pressure can cause systematic errors up to 1.5%, while fluctuations in the sealing liquid level due to temperature, evaporation, or vibration can cause errors up to 0.7%. These errors can be considerably reduced through automation of gas volume reproduction and gas meter verification. The authors have proposed to improve the systems for air pressure stabilization under the bell, control of sealing liquid level to compensate for its dynamic variation, and stabilization of air temperature during meter verification. У цій роботі виконано аналіз дзвонової установки для метрологічної перевірки витратомірів та лічильників газу, виділено її переваги та недоліки. На основі аналізу наукових джерел та результатів експериментальних досліджень дзвонових еталонних установок встановлено, що ці установки залишаються одним із найточніших засобів перевірки та калібрування лічильників газу. Проте їх метрологічні характеристики суттєво залежать від умов застосування, зокрема робочого тиску, рівня замкової рідини та температури середовища. Зміна робочого тиску може викликати систематичні похибки до 1,5%, зміна рівня замкової рідини під впливом температури, випаровування або вібрацій може спричинити похибку до 0,7%. Ці похибки можуть бути значно зменшені за допомого автоматизації процесів відтворення одиниці об’єму газу та перевірки лічильника газу. Пропонується удосконалити системи стабілізації тиску повітря під дзвоном, регулювання рівня замкової рідини для компенсації зміни рівня в динамічних процесах, стабілізації температури повітря під час процедури перевірки лічильників.